2018
DOI: 10.20546/ijcmas.2018.709.293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dates of Sowing on Incidence of Mungbean Yellow Mosaic Virus (MYMV) in Mungbean

Abstract: and Java (Singh, 1991). Mungbean is grown principally for its protein rich edible seeds which are used for consumption by cooking, fermenting, milling or sprouting. Seeds are also used for making soups, curries, bread, sweets, noodles, salads, papad etc. (Singh et al., 1988). It is one of the major sources of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although the disease incidence was slightly more as compared to D1 but the crop sown in this date had better plant growth and yield attributing characters which resulted in more seed yield as compared to other dates of sowing. In earlier studies, Meti and Kenganal (2018) [13] recorded highest yield of 1220 kg/ha when the green gram crop was sown in 6.…”
Section: Seed Yieldmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the disease incidence was slightly more as compared to D1 but the crop sown in this date had better plant growth and yield attributing characters which resulted in more seed yield as compared to other dates of sowing. In earlier studies, Meti and Kenganal (2018) [13] recorded highest yield of 1220 kg/ha when the green gram crop was sown in 6.…”
Section: Seed Yieldmentioning
confidence: 89%
“…Similar to the present investigation, Sarmah et al (2017) [21] also observed a negative significant correlation between whitefly population and maximum temperature, a negative nonsignificant correlation with minimum temperature but a positive non-significant correlation with Bright Sun shine hours. Meti and Kenganal (2018) [13] observed the least whitefly population during 40 th and 39 th SMW when the weekly mean maximum temperature was 28.9 °C and 30.4 °C, minimum temperature 22.8 °C to 22.2 °C and total weekly rainfall was 60.8 mm for 4 days respectively. They recorded highest number of whiteflies during 50 th SMW having 29.7 °C maximum temperature.…”
Section: Effect Of Meteorological Parameters On Whitefly Populationmentioning
confidence: 97%